Mathematics Learning Management: Kurikulum Merdeka at Islamic School - Muna, Robihah Munihatul; Windiaratri, Nur Azizah; Tuzzaro, Nahdia; Astuti, Wiwin (Journal of Education, Religious, and Instructions (JoERI), 2025)
This study aims to analyze the management of mathematics instruction under the Merdeka Curriculum at Madrasah Aliyah Al-Manshur Popongan, Klaten Regency, during the 2024/2025 academic year. A descriptive qualitative approach was employed, utilizing data collection techniques such as in-depth interviews and direct observations of the vice principal of curriculum and mathematics teachers, along with an analysis of relevant documents. The findings indicate that: (1) lesson planning is conducted systematically through the development of flexible and adaptive modules, although the integration of technology remains a challenge; (2) instructional implementation employs a differentiated approach with an emphasis on contextual projects, yet is hindered by regulations that restrict the use of digital tools; and (3) learning evaluation is oriented toward formative assessment, although technological limitations constrain the variety of assessment methods. The results highlight the importance of enhancing technological infrastructure and providing targeted teacher training to ensure the effective implementation of the Merdeka Curriculum and to improve educational quality in the madrasah.